Ship pipeline collaborative layout optimization based on EPA-star algorithm - Zhiyao YANG; Hongshuo ZHANG; Yan LIN (Zhongguo Jianchuan Yanjiu)
ObjectivesAiming to overcome the efficiency and engineering practicality issues of existing pipeline layout design methods, this study explores a high-efficiency EPA-star (escape pruning A-star algorithm) for pipeline layout optimization.MethodThe layout space is discretized based on the escape graph method, the resulting connection points are stored as the adjacency table, the estimated traversal cost and penalty function are introduced to reduce the bending and folding phenomenon in the path, and the path is pruned to improve the quality of paths in the case of large spans. A method of branching point selection for branch pipelines considering the forbidden region is proposed which improves the quality and efficiency of the path design. By improving the layout efficiency at the pipeline level within the collaborative strategy, a more effective collaborative layout algorithm can be achieved. ResultsThe feasibility and effectiveness of the EPA-star algorithm in the piping layout of conventional ships and its practicality in the complex layout of special ships are verified through the simulation examples of the nacelle fuel piping of real ships and the nacelle piping of nuclear-powered ships respectively, wherein the length of the piping is shortened by 0.52% and 35.41%, and the number of elbows is reduced by 32.3% and 6.5%, leaving more space for maintenance. The effect of the collaborative piping is more compact than that of the original engineering case, and the quality of the piping is significantly improved. ConclusionThe results of this study can provide useful guidance for the design of piping layout schemes for common ships and special ships.